PENGARUH PUPUK NPK YANG DIPERKAYA PUPUK HAYATI TERHADAP PERTUMBUHAN DAN HASIL BAWANG DAUN PADA TANAH GAMBUT - Fenandra, Adara; Darussalam, Darussalam; Susana, Rini; Warganda, Warganda; Ashari, Asri Mulya (Agros Journal of Agriculture Science, 2024)
Onion (Allium fistulosum L.) is one of the plants that is used as a spice in cooking. Leaf onions can be planted on peat soil, but to get good growth, proper fertilization is needed because of the low nutrient content in peat soil. The purpose of this study is to obtain the best dose of NPK fertilizer enriched with biofertilizer for the growth and yield of leeks on peat soils. This research was carried out in the experimental land of the Faculty of Agriculture, Tanjungpura University from February 2024 to May 2024. The method used was a Complete Random Design (RAL) which consisted of 5 levels of treatment that were repeated 4 times, each replicate consisted of 4 plant samples so that there were a total of 80 plants. The treatment levels used in this study are as follows: h1 = NPK 400kg/ha, h2 = NPK 350 kg/ha, h3 = NPK 300 kg/ha, h4 = NPK 250 kg/ha, h5 = NPK 200 kg/ha. The variables observed in this study were plant height, number of saplings per clump, fresh weight of plants, root volume, and dry weight of plants. The results showed that the application of NPK fertilizer enriched with biofertilizer at a dose of 200 kg/ha was the best dose and could streamline the use of NPK fertilizer by 50% of the NPK fertilizer dose of 400 kg/ha in increasing the growth and yield of onion on peat soil.